Air temperature changes in Serbia and the Belgrade heat island - Milovanović Boško (Zbornik Radova: Geografski institut "Jovan Cvijić", 2015)
Climatic regionalization of Serbia was performed in the paper on the basis of data on air temperature from 23 meteorological stations and using cluster analysis. Applying Mann-Kendall test and Sen's slope estimates, temperature linear trends were investigated within each of the clusters, but also at each station individually. It has been shown that a positive linear trend is present in practically entire territory of Serbia and that it is very strong in Belgrade. Differences in air temperature between Belgrade and the cluster in which it is located were examined on an annual basis. [Projekat Ministarstva nauke Republike Srbije, br. III 47007]